A 23-year retrospective review of heart transplant donor and recipient referrals to Groote Schuur hospital between 1997 and 2019 - Kanyongo, Rusununguko (Division of General Surgery, 2025)
Background. Heart transplantation in South Africa faces numerous challenges related to organ scarcity and unequal access to advanced heart therapy. There is an urgent need to analyse the current transplant referral pathway to optimise equitable access to transplantation. Objectives. To provide an audit of heart transplant referrals to Groote Schuur Hospital, Cape Town, over a 23-year period, focusing on patient demographics, indications for referral, waiting-list dynamics, and transplant referral outcomes. Methods. The study utilised a retrospective patient folder review for the period 1 January 1997 - 31 December 2019 and audited the trends in heart transplant referrals and associated outcomes of the referral at a tertiary academic hospital. Results. A total of 625 recipients were referred for heart transplantation, with the majority being male (n=412; 65.9%), while gender was undocumented for 69 cases (11.0%). The mean age was 38.1 (14.6) years, and 153 (24.5%) were listed for transplant, while 215 (34.4%) were deemed ineligible for listing. Contraindications for listing included social (n=106; 49.3%), medical (n=83; 38.6%) and psychological (n=26; 12.0%) factors, while 134 patients (21.4%) were considered too well. Poor social circumstances (n=38; 39.6%), poor insight (n=28; 29.2%) and poor compliance (n=21; 21.9%) were the most common non-medical reasons for not listing recipients, while obesity (n=30; 31.3%) and smoking (n=23; 24.0%) were notable medical contraindications. Forty-nine patients (7.8%) died during work-up, while 130 (85.0%) of the listed patients received a heart transplant. Of the 429 donor referrals, 139 (32.4%) were accepted for organ procurement. Reasons for declining donors included unsuitability for transplantation (30.3%), lack of capacity (1.8%), and recipient-donor mismatch (66.9%). Conclusion. Three-quarters of the referred patients were deemed unsuitable for heart transplantation for medical and/or social reasons. The ratio of referral to listing has decreased over time. However, once listed, the likelihood of receiving a transplant was high.